Case report:Multiple abscesses caused by Porphyromonas gingivalis diagnosed by metagenomic next-generation sequencing - Zhang, Yichen; Zhu, Youfeng; Wan, Huijuan (Frontiers in Medicine, 2023)
Background: Extraoral infection by Porphyromonas gingivalis (P. gingivalis) was extremely rare and hard to be diagnosed for the reason that the fastidious pathogen was hard to be cultured by traditional test. We reported the first case of a patient with multiple abscesses in muscles and brain with dura empyema due to P. gingivalis diagnosed by metagenomic next-generation sequencing(mNGS). Case description: A 65-years-old male patient was admitted to our hospital for multiple lumps in his body. By brain MRI and lower limbers CT test, A diagnosis of multiple abscesses in brain and muscles was made. P. gingivalis was detected by mNGS test in blood, CSF and pus samples as traditional bacterial culture in theses samples showed negative result. Target antibiotic therapy of meropenem and metronidazole and CT guided percutaneous catheter drainage of bilateral thighs abscesses were performed. The size of muscle abscesses reduced significantly and neurological function improved. Conclusion: Metagenomic next-generation sequencing(mNGS) is helpful for early diagnosis and subsequent treatment of P. gingivalis associated-multiple abscesses.